Leprosy in the elderly population of an endemic state in the Brazilian Northeast (2001-2017): epidemiological scenario, - Carlos Dornels Freire de Souza; Tânia Rita Moreno de Oliveira Fernandes; Thais Silva Matos; Clódis Maria Tavares (Sociedade Brasileira de Dermatologia, 2020)
Abstract This ecological study aims to analyze both the tendency and the characteristics of leprosy in the elderly population in the state of Bahia, 2001-2017. The tendency was analyzed through joinpoint regression. Epidemiological variables were also included in the study. The average detection rate was 38.73/100,000, with prevalence of men (45.19/100,000). A downward trend occurred in both genders, from 2004, with a greater magnitude in women (annual percent change [APC] = −3.4%). Men presented higher proportions of the multibacillary forms and physical disabilities. The epidemiological scenario indicates the need of implementation of actions that stimulate early diagnosis and treatment of the elderly population.